2023
DOI: 10.1002/adfm.202210268
|View full text |Cite
|
Sign up to set email alerts
|

Reconfigurable and Broadband Polarimetric Photodetector

Abstract: The sensitive detection of light polarization besides the intensity and wavelength, can provide a new degree of freedom for more and clearer information of imaging targets in night, fog, and smoke environment. However, the conventional filter-integrated polarimetric photodetectors suffer from the complicated fabrication process and limited spectral range. Herein, broadband and polarization-sensitive photodetectors are achieved with reconfigurable operation mode, utilizing the linear dichroism and narrow band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…As the key figures of merit of photodetectors, the response speed (τ rise : photocurrent increases from 10 to 90% of its final value)/decay time (τ decay : photocurrent falls from 90 to 10% of its beginning value), noise, and specific detectivity are also characterized. As displayed in Figure e, τ rise /τ decay values of 157/141 μs ( V g = −60 V) and 208/173 μs ( V g = 0 V) were obtained at a frequency of 100 Hz in Figure S8a–d. , The Fourier transform of the dark current traces gives the noise spectral density ( S n ) as a function of frequency, as shown in Figure S9b ( V g = 0 V) and Figure S9d ( V g = −60 V). ,, At low frequencies, a 1/ f noise component is observed, attributed to interface traps or defects, , whereas at high frequencies above 10 Hz, the device reaches a noise floor with very low white noise, about 2 × 10 –15 A Hz –1/2 , which is independent of the frequency and close to the scattered particle noise floor. Moreover, at V g = −60 V, a lower S n was obtained, probably due to MoTe 2 in the heterojunction being electrostatically tuned to P-type doping, creating a larger built-in electric field.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…As the key figures of merit of photodetectors, the response speed (τ rise : photocurrent increases from 10 to 90% of its final value)/decay time (τ decay : photocurrent falls from 90 to 10% of its beginning value), noise, and specific detectivity are also characterized. As displayed in Figure e, τ rise /τ decay values of 157/141 μs ( V g = −60 V) and 208/173 μs ( V g = 0 V) were obtained at a frequency of 100 Hz in Figure S8a–d. , The Fourier transform of the dark current traces gives the noise spectral density ( S n ) as a function of frequency, as shown in Figure S9b ( V g = 0 V) and Figure S9d ( V g = −60 V). ,, At low frequencies, a 1/ f noise component is observed, attributed to interface traps or defects, , whereas at high frequencies above 10 Hz, the device reaches a noise floor with very low white noise, about 2 × 10 –15 A Hz –1/2 , which is independent of the frequency and close to the scattered particle noise floor. Moreover, at V g = −60 V, a lower S n was obtained, probably due to MoTe 2 in the heterojunction being electrostatically tuned to P-type doping, creating a larger built-in electric field.…”
Section: Resultsmentioning
confidence: 86%
“…As displayed in Figure 5e, τ rise /τ decay values of 157/141 μs (V g = −60 V) and 208/173 μs (V g = 0 V) were obtained at a frequency of 100 Hz in Figure S8a−d. 35,36 The Fourier transform of the dark current traces gives the noise spectral density (S n ) as a function of frequency, as shown in Figure S9b (V g = 0 V) and Figure S9d (V g = −60 V). 4,37,38 At low frequencies, a 1/f noise component is observed, attributed to interface traps or defects, 4,37 whereas at high frequencies above 10 Hz, the device reaches a noise floor with very low white noise, about 2 × 10 −15 A Hz −1/2 , which is independent of the frequency and close to the scattered particle noise floor.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Above all, the reconfigurable polarization photodetection of our fabricated WTe 2 /WS 2 phototransistor under V g control can apply several modes such as polarimetric sensor or not dependent on the specific application circumstances. [67] Moreover, the imaging capability of a self-driven photodetector to collect optical signals and acquire high-resolution image information is of great importance in remote sensing detection. A light-emitting diode (LED) of 620 nm with a spot diameter of 27 μm at light power of 800 μW is implemented by a commercial single-pixel modulus (see in Measurement part).…”
Section: Resultsmentioning
confidence: 99%
“…[ 10 ] Above all, the reconfigurable polarization photodetection of our fabricated WTe 2 /WS 2 phototransistor under V g control can apply several modes such as polarimetric sensor or not dependent on the specific application circumstances. [ 67 ]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a superior linear DR of ≈18 has been realized upon 635 nm illumination. Most recently, Li et al have demonstrated self-powered polarizationresolved photodetection from visible to near infrared based on a b-As 0.4 P 0.6 /MoTe 2 heterojunction [124].…”
Section: D Vdwm Polarized Photodetectorsmentioning
confidence: 99%